THE DESIGN OF MERDEKA BELAJAR KAMPUS MERDEKA CURRICULUM AT STATE AND PRIVATE HIGHER EDUCATION IN CENTRAL JAVA (Review of Islamic Religious Education Curriculum) - Anas Rohman; Nurul Azizah; Zaim Elmubarok; Darul Quthni; Azka Nabila (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study examines the design of Merdeka Belajar Kampus Merdeka (MBKM) curriculum at the state and private higher education in Central Java (review of Islamic Religious Education curriculum). This research was a field study with a descriptive qualitative method. The data source was obtained by conducting interviews, observation, and documentation. Data analysis was done by grouping, reducing, presenting data, and drawing conclusions. The results showed that the design of MBKM PAI in Central Java had been divided into two forms. First, the design of MBKM is based on study programs, which in this design are usually run by Islamic tertiary institutions that have Islamic education study programs. In this design, the most obvious problem is the late completion of the final assignment, so the solution is to make the students work on their thesis in the seventh semester. Second, the MBKM design is based on subjects, which is usually done by public universities that do not have study programs PIE. So the readiness of students for field practice needs to be improved. Accordingly, it is necessary to make group assignments. Apart from that, the problem is the lack of credits, so additional tasks need to be addressed.